PEMBELAJARAN MENULIS TEKS EKSPOSISI DENGAN METODE BRAINSTORMING KELAS X - Dini, Sri Kamila; Riadi, Sugeng (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
This  study  aims  to  determine  leaming  to  write  an  exposition  text  using  the brainstorming  method  for students. The research  was carried out on class X IPS 1 students in the odd semester of the 2021/2022  school year.  The place of research is at Madrasah Aliyah Ar-Rifa’iah Bogor City. The formulation of the problem studied in this study is how to use the brainstorming method in leaming to write exposition text of class X students of Madrasah Aliyah Ar-Rifa’iah Bogor City,  odd semester of the 2021/2022 school year?. The method used in this research is descriptive qualitative. Data collection techniques in this study used several methods, such as observation, interviews, documentation, and tests. The aspects assessed in this  study were the content of ideas, structure, vocabulary, effective sentences, and spelling. The results showed that the average ability ofclass X IPS 1 students in leaming to write exposition texts using the brainstorming  method was 85.66  or rounded to 86. This value, if categorized in Burhan Nurgiyantoro's theory, got the predicate very good (A). This has a positive impact and makes it easy for students to write an exposition text.Keywords: Brainstorming Method, Writing Leaming, Exposition Text